2018
DOI: 10.1159/000488079
|View full text |Cite
|
Sign up to set email alerts
|

Noninflammatory Diffuse Follicular Hypertrophy/Hyperplasia of Graves Disease: Morphometric Evaluation in an Experimental Mouse Model

Abstract: Objectives: Experimental models of Graves hyperthyroid disease accompanied by Graves orbitopathy (GO) can be efficiently induced in susceptible inbred strains of mice by immunization by electroporation of heterologous human TSH receptor (TSHR) A-subunit plasmid. The interrelated pathological findings in the thyroid glands of Graves disease (GD) that explain the core changes classically include diffuse follicular hyperplasia and multifocal mild lymphocytic infiltrate. However, the relative contributions of diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Even if hypertrophy indicates an increase in cell size and hyperplasia indicates an increase in cell number, they frequently coexist, because they are triggered by the same stimulus such as hormones and/or growth factors (47). Since it was demonstrated that primary hypothyroidism with its associated increase of serum levels of TSH induces C cells hyperplasia (such hyperplasia being reversed by T4 administration) (30), the changes in number and size of C cells that we observed after Cd challenge could be related to the Cd-induced hypothyroidism (3,(19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%
“…Even if hypertrophy indicates an increase in cell size and hyperplasia indicates an increase in cell number, they frequently coexist, because they are triggered by the same stimulus such as hormones and/or growth factors (47). Since it was demonstrated that primary hypothyroidism with its associated increase of serum levels of TSH induces C cells hyperplasia (such hyperplasia being reversed by T4 administration) (30), the changes in number and size of C cells that we observed after Cd challenge could be related to the Cd-induced hypothyroidism (3,(19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%